The epidermal bladder cell‐free mutant of the salt‐tolerant quinoa challenges our understanding of halophyte crop salinity tolerance. Issue 4 (30th August 2022) - Moog, Max William; Trinh, Mai Duy Luu; Nørrevang, Anton Frisgaard; Bendtsen, Amalie Kofoed; Wang, Cuiwei; Østerberg, Jeppe Thulin; Shabala, Sergey; Hedrich, Rainer; Wendt, Toni; Palmgren, Michael
Summary: Halophytes tolerate high salinity levels that would kill conventional crops. Understanding salt tolerance mechanisms will provide clues for breeding salt‐tolerant plants. Many halophytes, such as quinoa ( Chenopodium quinoa ), are covered by a layer of epidermal bladder cells (EBCs) that are thought to mediate salt tolerance by serving as salt dumps. We isolated an epidermal bladder cell‐free ( ebcf ) quinoa mutant that completely lacked EBCs and was mutated in REBC and REBC‐like1 . This mutant showed no loss of salt stress tolerance. When wild‐type quinoa plants were exposed to saline soil, EBCs accumulated potassium (K + ) as the major cation, in quantities far exceeding those of sodium (Na + ). Emerging leaves densely packed with EBCs had the lowest Na + content, whereas old leaves with deflated EBCs served as Na + sinks. When the leaves expanded, K + was recycled from EBCs, resulting in turgor loss that led to a progressive deflation of EBCs. Our findings suggest that EBCs in young leaves serve as a K + ‐powered hydrodynamic system that functions as a water sink for solute storage. Sodium ions accumulate within old leaves that subsequently wilt and are shed. This mechanism improves the survival of quinoa under high salinity conditions.